2022
DOI: 10.1021/acscatal.2c03041
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Extended C4–Symmetric Dirhodium Tetracarboxylate Catalysts

Abstract: The synthesis and evaluation of six C4-symmetric bowl-shaped dirhodium tetracarboxylate catalysts are described. These elaborate high-symmetry catalysts are readily generated by means of the self-assembly of four C1-symmetric ligands around the dirhodium core. These catalysts are capable of highly site-selective, diastereoselective, and enantioselective C–H functionalization reactions by means of donor/acceptor carbene-induced C–H insertions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
(117 reference statements)
0
10
0
Order By: Relevance
“…Only a single set of ligand peaks was observed, suggesting a structure with a high degree of symmetry in solution, or perhaps rapid exchange dynamics. In either limiting case, a well-defined structure exists in both the solid state and in solution, providing a reasonable model for future catalyst design of next-generation dirhodium­(II) peptide complexes …”
Section: Resultsmentioning
confidence: 99%
“…Only a single set of ligand peaks was observed, suggesting a structure with a high degree of symmetry in solution, or perhaps rapid exchange dynamics. In either limiting case, a well-defined structure exists in both the solid state and in solution, providing a reasonable model for future catalyst design of next-generation dirhodium­(II) peptide complexes …”
Section: Resultsmentioning
confidence: 99%
“…The results of the four most significant catalysts related to this study are summarized in Table . The most broadly successful catalyst for asymmetric cyclopropanation with aryldiazoacetates is Rh 2 ( S - p- Ph-TPCP) 4 ( 9 ) but it also suffered from decreasing levels of enantioselectivity on increasing the amount of HFIP. ,, Rh 2 ( S-tetra-p- BrPhPTTL) 4 ( 10 ), a recently developed catalyst, retained excellent levels of enantioselectivity (98% ee) when up to 10 equiv of HFIP was used; however, when HFIP was used as a solvent, the enantioselectivity dropped to 72% ee. Unexpectedly, the best catalyst when HFIP is used as a solvent is Rh 2 ( S -NTTL) 4 ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the Rh 2 (S-tetra-(4-Br)TPPTTL) 4 catalyzed reaction of the aryldiazoacetate 7 with 5 strongly preferred the formation of the tertiary C−H functionalization product 8 over the primary C−H functionalization product 9 (>20:1 r.r. ), 25 discussed in an earlier publication. 34 The ligand self-assembles to generate C 4 -symmetric bowl-shaped structures, in which the 16 aryl rings on the periphery of the catalyst are tilted, leading to an induced helical chirality.…”
mentioning
confidence: 95%
“… The acceptor group ensures that the carbene is sufficiently electrophilic to be capable of reacting with C–H bonds, whereas the donor group modulates the reactivity, making the system highly susceptible to catalyst control. Various chiral dirhodium catalysts have been designed to control the regio- and stereochemical outcomes of their C–H functionalization reactions. , Most of the studies have been conducted using aryldiazoacetates as the carbene precursors, and selective reactions at primary, secondary, or tertiary C–H bonds can be achieved depending on which catalyst is used. Subtle control can be achieved by changing the nature of the donor and acceptor groups. For example, even though methyl esters 1 are effective carbene precursors for functionalization at activated C–H bonds (benzylic, allylic, α to oxygen or nitrogen), the trichloroethyl esters 2 are superior for reactions at unactivated C–H bonds. In order to further expand the scope of the C–H functionalization chemistry of donor/acceptor carbenes, we explored the use of phosphonates as the acceptor group ( 3 ), which opens up interesting possibilities because the resulting carbenes behave more sterically demanding than their ester counterparts.…”
mentioning
confidence: 99%